2024
DOI: 10.1186/s12985-024-02292-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genotypes analysis of human papillomavirus infection in Beijing, China

Jiao Wang,
Haotian Li,
Jieqiong Zhang
et al.

Abstract: Background This study aimed to investigate the epidemiology of high-risk human papillomavirus (HPV) in the female population in Beijing, China, and identify the relationship between HPV genotypes and host factors. Methods HPV testing was performed on women aged 15–89 (mean age 38.0 ± 10.9 years) from Beijing in 2020. High-risk HPV genotyping real-time polymerase chain reaction was used to determine HPV genotypes. The overall prevalence, age-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Similarly, to our finding the most aggressive HR-HPV in the development of cervical precancerous lesions and malignant cancer was HPV16 [38]. According to a recent study showed that among women in China, founded that HHPV16, HPV39, HPV51, and HPV52 the moist common high risk HPV were associated with CIN and HPV16 infection was especially worrying since it aggravates cervical lesions [39].…”
Section: Correlation Of Hpv Genotypes With Cervical Lesionssupporting
confidence: 67%
See 3 more Smart Citations
“…Similarly, to our finding the most aggressive HR-HPV in the development of cervical precancerous lesions and malignant cancer was HPV16 [38]. According to a recent study showed that among women in China, founded that HHPV16, HPV39, HPV51, and HPV52 the moist common high risk HPV were associated with CIN and HPV16 infection was especially worrying since it aggravates cervical lesions [39].…”
Section: Correlation Of Hpv Genotypes With Cervical Lesionssupporting
confidence: 67%
“…Molecular detection of HR-HPVs was achieved by isolation and purification of DNA from specimens and followed by amplification of 14 specific high-risk HPV genotypes (16,18,31,33,35,39,45,51,52,56,58,59, 66, 68) using real-time PCR (kit packed from Sacase, Italy) in the urogenital swabs and biopsies. Genomic DNA was extracted from cervical swabs in VTM by using the DNA-Sorb-A (Sacase, Italy) nucleic acid extraction kit according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations